Voorhis Unit Field Trip [film footage of San Luis Obispo and Voorhis Unit, circa 1940]
Film footage of instructional activities and facilties at the San Luis Obispo campus and the Voorhis Unit of California Polytechnic State College. The Voorhis Unit, located in San Dimas, California, was donated by Charles and Jerry Voorhis in 1938 as a horticulture training center. [00:00:15] Views of a farm outdoors, San Luis Obispo campus, and Bishop Peak [00:00:26] Several men wash down hogs in a pen and move them to a different pen [00:01:00] A truck drives through a gate and onto a cow field [00:01:42] The cows are fed by the men in the truck [00:02:00] A man tills a field with several flowers and bushes [00:02:20] Two men load plants into a greenhouse and arrange flower pots [00:03:00] View of the interior of the greenhouse as the men arrange flowers [00:03:33] Men in front of the Agricultural Mechanics building assemble a tractor [00:04:00] Blacksmith shop and woodworking shop are shown [00:04:44] Horses shown walking in a field [00:05:26] Two men attach bridles to horses and lead them out of the field [00:05:48] Horses shown in a stable and in a corral [00:06:15] View of students eating in the cafeteria [00:06:40] Students walk into the Aeronautics Department and work on machines [00:07:09] Two men assemble the wing of a glider or airplane [00:08:30] Students continue to work on assembling an airplane [00:08:50] A student walks into the Electrical Engineering department and works on copper wire [00:09:16] Several large machines are shown [00:09:37] A man climbs a telephone pole and attaches wire to it [00:10:00] Air-Conditioning laboratory shown [00:10:57] A machine shop is shown [00:11:27] Many welders are working on a large work table [00:11:47] Voorhis Unit title card and buildings shown [00:11:52] Chapel at Voorhis unit [00:12:45] Shots of campus continue [00:13:25] Students are shown working on various agricultural tasks [00:14:40] Several people harvest fruit from an orchard [00:15:00] Students on a field trip go into a field with clipboards and take notes